Autonomy and Disability: The Challenges Associated with Understanding the Exercise of Autonomy that Motivate the Formulation of Bioethics Applied to Disability (Revista Iberoamericana de Bioética, 2023)
Performing an objective analysis of the exercise of autonomy in a person with a disability can be very complex if one considers beforehand the significant burden of discomfort derived from the limitations endured by the individual, secondary to the very nature of his/her condition, and the external mediators implied. Reviewing theoretical concepts on the possible variables at play in disability decision-making can provide a more accurate view on the difficulty of undertaking a bioethical assessment of the situation, avoiding falling into the trap of prejudice or not giving the appropriate value to the manifestation of the person’s self-will, scenarios with a significant impact on clinical bioethics.
Keywords: autonomy; disability; bioethics; disability bioethics; quality of life; adaptative preferences